Analytical and a numerical ground resonance analysis of a conventionally articulated main rotor helicopter - Eckert, Bernd (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.